주요우울장애 노인에 대한 Internet of Things 기반 행동 중재 : 예비연구 - 한효진; 홍창형; 김재훈; 노현웅; 손상준 (노인정신의학, 2019)
Objective：To assess the effectiveness of Internet of Things (IoT)-based behavioral intervention for reducing depressive symptom of older adults with major depressive disorder. Methods：A 12-week randomized cross-over controlled study was conducted at community mental health center. We recruited 39 participants with major depressive disorder aged 60 years or older. As a multidomain intervention, four evidence-based therapeutic factors (physical activity, healthy diet, social activity, and emotional regulation) were approached. To maintain motivation of participants, we applied contingency management using IoT device based on operant conditioning theory. Results：The primary outcome was change of depressive symptom measured by Montgomery-Asberg Depression Rating Scale (MADRS). Mixed-effect model compared the effectiveness of intervention and usual care management (intervention by time and period interaction, p=0.017). And during the study period consisting of a total of visit 8, significant group difference was shown in post hoc test at visit 4 (MADRS score of intervention group : MADRS score of control group=7.7±3.4 : 21.1±11.5, p=0.008). Conclusion：Community-implementable IoT-based behavioral intervention resulted in greater reduction of depressive symptom of elderly with major depressive disorder
Keywords: Depression; Elderly; Internet of things; Psychosocial intervention.